Peran Modal Sosial dalam Usaha Tani Kopi Arabika di Desa Kendenan Kecamatan Baraka Kabupaten Enrekang - Anwar Anwar; Abd Rahim; Muhammad Syafri (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
This research aims to determine the role of social capital in Arabica coffee farming in Kendenan Village, Baraka District, Enrekang Regency. This research uses a purposive sampling technique for taking informants, namely informants who are determined deliberately. The data analysis technique used is qualitative, including data reduction analysis, data presentation and drawing conclusions. The results of this research show that coffee farmers in Kendenan Village have a high element of trust by adopting an honest, open and respectful attitude. Social norms still apply in developing Arabica coffee farming, farmers are limited by rules that are understood verbally or unwritten. We can see the close social network through communication and cooperation that is built between fellow farmers, traders and extension workers. The reciprocal relationship between Arabica coffee farmers helps each other, pays attention to each other and helps each other, making it easier to complete work in coffee farming. The role of social capital in developing coffee farming is transaction costs, sharing information, collective decision making